Yaoshania and Erromyzon kalotaenia, a new genus and a new species of balitorid loaches from Guangxi, China (Teleostei: Cypriniformes) - Yang, Jian; Kottelat, Maurice; Yang, Jun-Xing; Chen, Xiao-Yong (Zootaxa, 2012)
Yaoshania, new genus, is described with Protomyzon pachychilus as type species. Yaoshania is distinguished from othergenera of Balitoridae by its larger gill opening, a lip lamina at angle of mouth, and the rostral fold with four notches toaccommodate rostral barbels. A lectotype is designated for Y. pachychilus. Erromyzon kalotaenia, new species, is de-scribed from Guangxi, China. It is distinguished from other species of Erromyzon by the very reduced median lobe of therostral fold; the lower lip distinctly covered with melanophores; and the color pattern on the flank. A key to the species of Erromyzon is provided.